2019
DOI: 10.1136/bmj.l5047
|View full text |Cite
|
Sign up to set email alerts
|

Post-finasteride syndrome

Abstract: Efforts to explain persistent symptoms are undermined by poor long term data on harms

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 13 publications
0
18
0
Order By: Relevance
“…Several studies have substantiated that FIN increases the risk for depressive symptoms in a subset of vulnerable patients [16,17,18]. In addition, several patients have reported that these psychological complications can persist even after FIN discontinuation [18,19,20,21,22,23], prompting some authors to coin the term “post-finasteride syndrome” (PFS) to define this condition. Altogether, this emerging evidence has led several national agencies to issue warnings about the potential for depression and other psychological sequelae [22,23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have substantiated that FIN increases the risk for depressive symptoms in a subset of vulnerable patients [16,17,18]. In addition, several patients have reported that these psychological complications can persist even after FIN discontinuation [18,19,20,21,22,23], prompting some authors to coin the term “post-finasteride syndrome” (PFS) to define this condition. Altogether, this emerging evidence has led several national agencies to issue warnings about the potential for depression and other psychological sequelae [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiology of PFS and other psychological complications of FIN remain unclear, in view of selection bias in many published clinical studies and high nocebo effect, as well as suboptimal safety information [22,23]. A full characterization of the behavioral effects of FIN is particularly important, given that preliminary reports have indicated that FIN may also have therapeutic properties for several neuropsychiatric conditions characterized by poor impulse control and excessive externalizing manifestations, including Tourette’s syndrome and pathological gambling [2,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Men on finasteride should be counselled about the possibility of these adverse effects and warned that unwanted symptoms can persist after treatment discontinuation, the origin of which remains unclear. Patients should be referred to psychology services for relevant therapeutic interventions 99 …”
Section: Post‐finasteride Syndrome and Anabolic Androgensmentioning
confidence: 99%
“…Kaplan et al [104] reported that a chronic treatment (5 years) with dutasteride induces a higher incidence of erectile dysfunction and gynecomastia than finasteride. Cases of persistent sexual dysfunction have been recently reported after the discontinuation of finasteride [32,60,97,99,100,129,131,134,141,147,149,166,170]. Irwig and Kolukula [99], using the Arizona Sexual Experience Scale (ASEX) validated questionnaire, interviewed 71 healthy male (21-46 years) finasteride-users, finding a high incidence of sexual dysfunction (Tables 6 and 7).…”
Section: -Arimentioning
confidence: 99%
“…Gur et al [30] report instead that the true prevalence of sexual side effects with 5-ARI treatment is currently unknown. (D) There have been recent reports of persistent sexual dysfunction after discontinuation of finasteride treatment [32,56,60,97,99,100,129,131,134,141,147,149,166,170,237]. Several authors have considered gynecomastia as a sexual dysfunction.…”
Section: Dutasteride (A) (B) (C) Finasteride (A) (B) (C) (D)mentioning
confidence: 99%